2002
DOI: 10.1161/hs0202.102335
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Anxiety, and Depression in Patients With an Untreated Intracranial Aneurysm or Arteriovenous Malformation

Abstract: Background and Purpose-The objective of this study was to assess the health-related quality of life and symptoms of anxiety and depression in patients who are aware of the presence of a patent aneurysm or arteriovenous malformation. Methods-Participants were retrospectively identified and invited to participate in the study; consenting participants were interviewed in a face-to-face setting by means of 2 questionnaires assessing health-related quality of life (Sickness Impact Profile [SIP] and the MOS Short F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 13 publications
7
45
1
Order By: Relevance
“…It is easy to spread biased information for commercial purposes on the Internet. 30) The present study revealed that only 2.6% of 1225 institutions in Japan disclosed outcome data of treatment for unruptured intracranial aneurysms on websites. This number is lower than we had expected when we launched this study.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…It is easy to spread biased information for commercial purposes on the Internet. 30) The present study revealed that only 2.6% of 1225 institutions in Japan disclosed outcome data of treatment for unruptured intracranial aneurysms on websites. This number is lower than we had expected when we launched this study.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, many papers report that the Internet is becoming the most important source of information for patients. 1,28,30,33) On the other hand, outcome disclosure is not easy from the viewpoint of hospitals and physicians that are subject to disclose information to the public. Complicated problems arise when information about medical outcomes are disclosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In elderly patients, this anxiety is more marked, and many patients report this anxiety as mental stress. [13][14][15] SAH with ruptured cerebral aneurysm more frequently leads to a serious condition in elderly patients, making it difficult to maintain pretreatment ADLs after rupture; 12) in addition to the characteristics of SAH, protracted-bedrest-related cognitive dysfunction or disuse progression 16,17) may affect subsequent recovery in elderly patients. [18][19][20] In many cases, the treatment indication for unruptured cerebral aneurysms in non-elderly patients is evaluated based on the location, size, and shape of aneurysms.…”
Section: Treatment Results: Complicationsmentioning
confidence: 99%
“…Quality of life (QOL) score was also analyzed in several outcome studies. 27,39,44) Some reported significant decline of QOL long time after aneurysm repair. However, preoperative anxiety was relieved by the repair of the aneurysm and QOL also improved.…”
Section: Management Outcome and Risksmentioning
confidence: 99%